Dual immune effect of iNKT cells considering human cutaneous and visceral leishmaniasis: An example of cell plasticity according to different disease scenarios. (June 2018) - Gois, B. M.; Peixoto, R. F.; Maciel, B. L. L.; Gomes, J. A. S.; de Azevedo, F. L. A. A.; Veras, R. C.; de Medeiros, I. A.; de Lima Grisi, T. C. S.; de Araújo, D. A. M.; do Amaral, I. P. G.; Keesen, T. S. L.
Abstract: Although the semi‐invariant natural killer T cells (iNKT) are a small subpopulation of cells in the peripheral blood, they are presumed to play a role in early stages of infection against various pathogens, including protozoa. This work investigates the activation status and cytokine profile of iNKT cells during human Leishmania infantum and Leishmania braziliensis infection. We studied iNKT cells in patients with symptomatic active visceral leishmaniasis (AVL) (n = 8), patients with symptomatic active cutaneous leishmaniasis (ACL) (n = 13), negative endemic controls (NEC) (n = 6) and non‐endemic controls (NonEC) (n = 6), with and without total Leishmania antigen stimulus (TLA). The number of iNKT cells in the peripheral blood of patients with ACL and AVL unaltered in relation to control groups. Moreover, the iNKT cells from ACL showed a hyperactivation profile compared to patients with AVL. Additionally, TLA induced IFN‐gamma production in iNKT cells from patients with ACL, while in iNKT of patients with AVL, TLA induced a decrease in this cytokine. Higher IL‐17 and IL‐10 production by iNKT cells from patients with ACL were also observed compared to all other groups. There were no changes in iNKT IL‐10‐producing cells in AVL after TLA stimulation. However, TLA induced increase in IL‐10 in iNKT cells in patients with ACL. These findings suggest that, although iNKT cells showed distinct profiles in patients with ACL and AVL, they play a dual role in immune modulation in both Leishmania infections.